The Role of the Family in Fostering Children's Interest in Reading as an Implementation of Family Literacy - Indra Rasyid Julianto; Annisa Sauvika Umami (West Science Interdisciplinary Studies, 2023)
This article examines families’ role in fostering children's interest in reading. Especially the literacy provided by the family is certainly a separate implementation empowered by the family. Parents who have outward duties in fostering, leading, and managing the care of children. Parents can guide children's cognitive character to mental strength, and morals, and also drive literacy empowerment or interest in reading in children. Literacy in children focuses on reading and writing activities from an early age. these activities can be called pre-reading and pre-writing activities. The subjects in this study are two families who have children in preschool age, 0-6 years old range in Lending Village, Cidadap District, Bandung City. Data collection techniques in this research are interviews, surveys, and documentation. Then the data analysis techniques in this study are data collection, data reduction, data presentation, and conclusions. Based on the results of the study, the success of reading and literacy culture in children is influenced by the family environment that shapes it. The more positive stimulations and influences given to children, such as vocabulary introduction and support for reading, the faster children can understand the writing they read and this can encourage the success of a literacy culture in the family.